Macroparticles in beam-plasma systems - Bizyukov, A.A.; Girka, I.O.; Romashchenko, E.V.; Chibisov, O.D. (Вопросы атомной науки и техники, 2016)
The macroparticle (MP) contamination is the most important technological problem of vacuum arc deposition of coatings. The results of theoretical study of MP charging and dynamics in the near-substrate sheath are presented. The charge and dynamics of MP are governed by local parameters of ion and secondary electron emission fluxes in the sheath. It is shown that the maximum possible velocity of repelled MP increases with increasing substrate bias voltage. The effect of substrate biasing is seen to be larger for MPs emitted at small angles to the cathode plane of arc evaporator. Наиболее важной технологической проблемой вакуумно-дугового осаждения покрытий является загрязне- ние макрочастицами (МЧ). Представлены результаты теоретического исследования зарядки и динамики МЧ в слое у подложки. Заряд и динамика МЧ определяются локальными параметрами ионных и электронных вторично-эмиссионных потоков в слое. Показано, что максимально возможная скорость отраженной МЧ возрастает с увеличением потенциала подложки. Эффект смещения потенциала подложки больше для МЧ, которые эмитируют под малыми углами к плоскости катода вакуумного испарителя. Найбільш важливою технологічною проблемою вакуумно-дугового осадження покриттів є забруднення ма- крочастинками (МЧ). Представлено результати теоретичного дослідження зарядки та динаміки МЧ у шарі біля підкладки. Заряд і динаміка МЧ визначаються локальними параметрами іонних та електронних вторин- но-емісійних потоків у шарі. Показано, що максимально можлива швидкість відбитої МЧ зростає зі збіль- шенням потенціалу підкладки. Ефект зсуву потенціалу підкладки більший для МЧ, які емітують під малими кутами к площині катоду вакуумного випарника.